ARTIFICIAL INTELLIGENCE IN JURISPRUDENCE: PROSPECTS AND PROBLEMS - Письменна, Олена; Лаврентій, З.О. (Modern engineering and innovative technologies, 2024)
Artificial intelligence (AI) is rapidly penetrating all areas of life, and jurisprudence is no exception. The application of AI in the legal field can significantly increase its effectiveness, but it also brings with it a number of problems that need to b